UN PROGRAMA PARA CALCULAR LAS REPRESENTACIONES IRREDUCIBLES DE SN, EN LA FORMA SEMINORMAL DE YOUNG 1 MATEMÁTICA COMPUTACIONAL COMO APOYO A LA DOCENCIA (2013)
The matrices of the irreducible representations of a group G are useful to compute the generalized FourierTransformof a function deflned on G. There are many other applications for the irreducible representations of a group. Wedeveloped a computer prograrn for computing the matrices of the irreducible representations of the symmetricgroup in the Young's serninormal form. This prograrn runs on the Computational Algebraic System CoCoA.